Electrochemical hydrogen evolution and storage studies on bismuth nano hexagons. (22nd November 2018) - Gupta, Sandeep; Singh, Rini; Agarwal, Garima; Ray, Kanad; Kothari, S.L.; Verma, Ajay S.; Saraswat, Vibhav K.; Awasthi, Kamlendra; Kumar, Manoj
Abstract: Bismuth nano hexagons were synthesized using potentiostatic electrodeposition and studied for their performance towards electrochemical hydrogen storage and evolution. Regular hexagons with edge length ≈ 500 nm and thickness ≈ 80 nm were observed in scanning electron microscopy (SEM). X-ray diffraction (XRD) pattern indicates the presence of poly-crystalline bismuth and bismuth oxide in rhombohedral and cubic phases respectively. X-ray photoelectron spectroscopy (XPS) studies further confirm the presence of two phases of bismuth i.e. elemental bismuth and bismuth (III) oxide. Results indicate that these nano hexagons show good hydrogen ion (H + ) storage and successive hydrogen gas (H2 ) evolution characteristics.